Dais Responsibility for The Environment of Peat lands In Islamic Perspective - Hendra Maujana Saragih (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This paper seeks to emphasize that Dai has serious religious responsibility for environmental damage that has occurred in Indonesia, especially in seven provinces that have peat areas. For those environmental damages, whether intentional or unintentional by anyone, even any group, even the State, was the target of the Da'i's preaching, of course. Dai in the peat land who can preach is one who has participated in training and workshops and is in accordance with his ability to broadcast MUI fatwas on the environment, ecosystems, forests and land fires. The theory used in this paper is da'wah and local train theory whose material content strongly refers to the fatwa of the MUI. The purpose of this paper is to find out the dais religious response to the environment of peat land in an Islamic perspective and dai's serious efforts in preaching is a form of religious and social responsibility carried out by Dai and this is necessary to get serious support also from all walks of course.